STRATEGIES FOR NURSING STUDENTS IN ACHIEVING BASIC NURSING COMPETENCIES THROUGH SELF-DIRECTED LEARNING READINESS - Astuti, Anggia; Abidin, Zainal; Wijaya, Dodi; Fibriansari, Rizeki Dwi; Yuliani, Nur (Nurse and Health: Jurnal Keperawatan, 2024)
Background: Clinical practice learning is designed to prepare nursing students to become professional nurses, students are required to meet competency achievement targets. To comprehensively achieve these targets, students must employ effective learning strategies, one of which is Self-Directed Learning Readiness. Objectives: To explore the strategies nursing students use to meet basic nursing competencies through Self-Directed Learning Readiness. Methods: This research used a quasi-experimental design with a one-group pretest-posttest model with total sampling, about 91 respondents of second-semester students from the Diploma 3 Nursing Program who conducted clinical practice. The intervention was carried out during the basic nursing clinical practice, with the approach of the stages in SDLR (plan-implementation-monitoring-evaluation). Respondents were given daily journaling which was filled in every day regarding the plan, implementation, monitoring, and evaluation of 58 basic nursing competency achievements. After the basic nursing clinical practice ended, respondents completed the post-test questionnaire. Data analysis was performed using an independent sample t-test. Results: The results showed that the majority of students achieved excellent scores (91%) in meeting basic nursing clinical practice competencies. The competency assessment covers three main aspects: knowledge, attitude, and psychomotor skills, with average scores of 82, 84.3, and 83, respectively. The results of statistical tests using the Independent T-Test showed that there was a positive effect of SDLR on the Competency Achievements of Basic Nursing Clinical Students with a p-value <0.05. Conclusion: Students with higher levels of SDLR tend to be more independent in managing time, utilizing various learning resources, and practicing clinical skills. The basic competencies achieved include cognitive, affective, and psychomotor aspects, reflecting their readiness to provide comprehensive nursing care.